Associations between inflammatory bowel diseases and vitamin D. Issue 8 (28th April 2019) - Barbalho, Sandra Maria; Goulart, Ricardo de Alvares; Gasparini, Rodrigo Gallhardi
ABSTRACT: Inflammatory Bowel Diseases (IBD) are increasing sharply, and the common medications are not effective for most patients. Vitamin D (VD) has been considerate to reduce inflammatory processes and may be helpful in IBD. The aim of this review was to perform an update on the potential role of VD in the IBD. We performed a search for articles associating VD and IBD published in MEDLINE-PubMed and EMBASE. The focused question used for the search was "What is the association between Inflammatory Bowel Disease and Vitamin D?" The exclusion criteria for this search were studies not in English, editorials, case reports, or poster presentations. VD prevents the inflammatory process such as negatively interfering with the release of Interleukin (IL)-1, IL-6, and Tumour Necrosis Factor-α; enhancing the function of the intestinal epithelial barrier; decreasing the occurrence of apoptosis; stimulating Toll-Like Receptor-4; inducing the production of an antimicrobial peptide in Paneth cells. Furthermore, deficiency of VD is related to the severity of the symptoms and increased the risk of cancer and surgery. In conclusion, VD shows a potential role in the management of IBD, the supplementation is inexpensive, safe, and leads to improvement of the quality of life.